Comercio internacional de servicios de salud para la población migrante y sus familias - Jiménez Nagore, Norma (Universidad Michoacana de San Nicolás de Hidalgo, 2006)
International trade in services is directly linked with immigration flows between Mexico and the United States and is consolidated by the formation of binational communities. Immigrants demand several types of services and those related with health issues stand out among the most important. Nevertheless, their migratory status disregards them as candidates for welfare services in the US, making them subject of increased expenses in private medical attention, or they may be forced to attend mexican health institutions where they receive limited quality attention. Therefore, prepayment schemes represent ideal means to provide health services and reduce finantial burden associated to private medical attention. In order to determine the importance of medical services, and specifically the possibility for medical insurance becoming viable alternatives to guarantee physical wellbeing, this research project included 380 immigrants from the state of Michoacan, Mexico. This sample was representative from the 39,200 immigrants from Michoacan who travel to the United States of America annually. The results obtained were analyzed with statistical methods –mean, rates, standard deviation, viariance, Spearman’s correlation coefficient- in order to determine the demand for medical services among this population and also to establish a business strategy which was evaluated through financial models. From these studies, it was observed that immigrants use 20% o their income to fulfill health needs and require medical assistance more than 5 times a year. In addition, the immigrants interviewed expressed their interest in buying medical inssurance but only if the price was low and if they hadn’t already hired one. It is important to mention that the quality provided by government health institutions in Mexico doesn’t constitute itself as a crucial factor that influences the buying process.

El comercio internacional de servicios se encuentra directamente vinculado con los flujos migratorios y se consolida con la formación de comunidades binacionales entre México y los Estados Unidos. Los migrantes demandan diversas clases de servicios entre los cuales destacan los relativos a la salud. Sin embargo, su situación migratoria les impide ser sujetos a la seguridad social de aquél país y se ven obligados a incurrir en gastos elevados para la atención médica en instituciones privadas, o bien acuden a las instituciones de salud mexicanas caracterizadas por su deficiente calidad. Ante esta situación, los esquemas de prepago se constituyen como los medios idóneos para disminuir la carga financiera que se deriva de la contratación de estos servicios. Para determinar la importancia de los servicios médicos, y en específico la posibilidad de que los seguros médicos puedan ser alternativas viables para garantizar su bienestar físico, se llevó a cabo un estudio que incluyó a 380 migrantes del estado de Michoacán. Dicha muestra se obtuvo de una población de 39,200 michoacanos que emigran a los Estados Unidos anualmente. Los resultados fueron sujetos a análisis estadístico –promedio, porcentaje, desviación estándar, varianza, coeficiente de correlación de Spearman- para determinar la demanda que tienen los servicios médicos en dicha población y crear una estrategia empresarial evaluada a través de modelos financieros se observó que los migrantes destinan el 20% de su ingreso para cuestiones médicas y requieren de estos servicios más de 5 veces al año. Además, al aplicar el coeficiente correlacional de Spearman para obtener la significancia de las variable se pudo observar, en general, los encuestados reconocieron estar interesados en adquirir algún tipo de seguro médico si su precio fuera reducido.
Instituto de Investigaciones Económicas y Empresariales. Maestría en Ciencias en Comercio Exterior
Keywords: info:eu-repo/classification/cti/5; ININEE-M-2006-0006; Sector salud; Servicios de salud; Migrantes; Portafolio de servicios; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/903